2014
DOI: 10.1039/c3np70102f
|View full text |Cite
|
Sign up to set email alerts
|

The vinylogous Mukaiyama aldol reaction (VMAR) in natural product synthesis

Abstract: The vinylogous Mukaiyama aldol reaction (VMAR) allows efficient access to larger segments for complex natural product synthesis, primarily polyketides, through the construction of vicinal hydroxyl and methyl groups as well as di and tri-substituted double bonds in one single operation. In this review, we will highlight stereoselective protocols that have been used in natural product synthesis and cluster them into the four groups that can be obtained from different silyl ketene acetals or enol ethers. At the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 126 publications
(98 reference statements)
4
51
0
Order By: Relevance
“…[6] Interestingly, we found that the ratios correlating to the dand l-cysteine derivatives are inverted compared with the corresponding serine analogues. A comparable scenario was found in Kobayashi-modified Mukaiyama aldol addition reactions [10] with 1,3-dithianyl acetaldehyde. The cysteine derivatives, on the other hand, seem to prefer the corresponding Cram-chelate products.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…[6] Interestingly, we found that the ratios correlating to the dand l-cysteine derivatives are inverted compared with the corresponding serine analogues. A comparable scenario was found in Kobayashi-modified Mukaiyama aldol addition reactions [10] with 1,3-dithianyl acetaldehyde. The cysteine derivatives, on the other hand, seem to prefer the corresponding Cram-chelate products.…”
Section: Resultssupporting
confidence: 72%
“…We reasoned that this behavior was due to the superior stability of the Ti-S bond, also exploited by Crimmins et al in their aldol reactions with oxazolidinethiones, [9] which resulted in the stabilization of a sterically unfavorable tricoordinated transition state ( Figure 1). A comparable scenario was found in Kobayashi-modified Mukaiyama aldol addition reactions [10] with 1,3-dithianyl acetaldehyde. [11] In this case syn instead of anti products with inverted diastereofacial selectivity were obtained.…”
Section: Resultssupporting
confidence: 66%
“…The synthesis of asymmetric β‐hydroxy carbonyl compounds has enjoyed its lion's share of problems addressed throughout the history of organic synthesis. Asymmetric β‐hydroxy carbonyl compounds are largely accessed through the aldol reaction,1 which is arguably the simplest and most economic approach to C–C bond formation,2 and has flourished over the years as a powerful tool for the synthesis of stereochemically complex molecules 3,4. However, despite many advances, acetaldehyde, the simplest aldehyde, largely remains unexplored in this reaction owing to difficulties in its handling and dual reactivity, that is, it may act as an electrophile as well as a nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Thes tereochemically defined and highly reactive bridgehead radical generated from the oxabicyclo[2.2.2]octane 3 would undergo a7 -endo cyclization into 2 with aC 9stereospecific connection of the hindered bond. [15] Subsequent vinylogous Mukaiyama aldol reaction of 6 by the action of BF 3 ·OEt 2 and CH(OMe) 3 [16] attached the dimethyl acetal group at the C13 position in an anti-selective manner to the bulky C14 isopropenyl group,l eading to 7 as the major product (d.r. Pattern recognition of the b-oriented isopropenyl cyclohexane substructure within 4 led us to utilize (R)-carvone (5)a st he starting material.…”
mentioning
confidence: 99%
“…Treatment of 5 with TMSCl and MeMgBr in the presence of catalytic FeCl 3 regioselectively produced the dienoxysilane 6. [15] Subsequent vinylogous Mukaiyama aldol reaction of 6 by the action of BF 3 ·OEt 2 and CH(OMe) 3 [16] attached the dimethyl acetal group at the C13 position in an anti-selective manner to the bulky C14 isopropenyl group,l eading to 7 as the major product (d.r. = 5:1).…”
mentioning
confidence: 99%